How important are school principals in the production of student achievement?. (30th July 2014) - Dhuey, Elizabeth; Smith, Justin
Abstract: As school leaders, principals can influence student achievement in a number of ways, such as hiring and firing of teachers, monitoring instruction and maintaining student discipline, among many others. We measure the effect of individual principals on gains in math and reading achievement between grades 4 and 7 using a value‐added framework. We estimate that a one standard deviation improvement in principal quality can boost student performance by 0.289 to 0.408 standard deviations in reading and math, while the principal at the 75th percentile improves scores by 0.170 to 0.193 relative to the median principal. Our results imply that isolating the most effective principals and allocating them accordingly between schools can have a significant positive effect on reducing achievement gaps. Résumé: Quelle importance ont les directeurs d'école dans la production du succès des étudiants ? En tant que leaders, les directeurs d'école peuvent influencer les résultats des étudiants de nombreuses manières, par exemple en engageant et renvoyant des enseignants, en surveillant le processus d'instruction, en maintenant la discipline dans le corps étudiant, etc. On mesure l'effet de directeurs particuliers sur les gains faits en mathématiques et lecture entre la 4 e et la 7 e années en utilisant un cadre conceptuel de valeur ajoutée. On estime qu'une amélioration de la qualité du directeur d'un écart‐type peut accroître la performance de l'étudiant en lecture et en mathématiques de 0.289 à 0.408 écart‐type, alors que le directeur se situant au 75 e percentile améliore les scores de 0.170 à 0.193 par rapport au directeur médian. Ces résultats signifient que d'identifier les directeurs les plus efficaces et de les répartir de manière appropriée entre les écoles peut avoir un effet positif significatif sur la réduction des écarts de performance.